УЎК 378.046.4 ПРОФЕССИОНАЛ ТАЪЛИМДА ПЕДАГОГЛАРНИНГ МАЛАКАСИНИ ОШИРИШДА ХОРИЖ ТАЖРИБАСИ - Султанов, Е.К. (SCIENCE and SOCIETY, 2022)
In this article, one of the necessary conditions and key issues of reforming vocational education in Uzbekistan is to increase the professional competencies of teachers, the training of teaching engineers who meet modern requirements.